2020
DOI: 10.1016/j.jbusres.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Individual capital and social entrepreneurship: Role of formal institutions

Abstract: We would like to thank the Editors and the two anonymous reviewers for their insightful comments and suggestions during the review process. They have engaged in a constructive dialogue and this has helped us to improve the manuscript substantially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(134 citation statements)
references
References 170 publications
7
108
0
Order By: Relevance
“…Brieger and De Clercq (2019) document that household income is negatively associated with entrepreneurs' social value creation goals. On the contrary, Pathak and Muralidharan (2016) and Sahasranamam and Nandakumar (2018) At the country level, we control for GDP per capita, GDP growth, and unemployment. and Brieger and De Clercq (2019) provide evidence for a positive relationship between GDP and socially oriented entrepreneurial activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brieger and De Clercq (2019) document that household income is negatively associated with entrepreneurs' social value creation goals. On the contrary, Pathak and Muralidharan (2016) and Sahasranamam and Nandakumar (2018) At the country level, we control for GDP per capita, GDP growth, and unemployment. and Brieger and De Clercq (2019) provide evidence for a positive relationship between GDP and socially oriented entrepreneurial activity.…”
Section: Methodsmentioning
confidence: 99%
“…This study expands this literature by focusing on formal institutions and how the quality of formal institutions moderates the relationship between an entrepreneur's age and his/her choice to create social value with his/her venture. While we do not believe that informal institutions or even socioeconomic development play subordinate roles compared to formal institutions in the relationship between entrepreneurs' age and social value creation, we focus on formal institutions previously shown as instrumental to understanding social entrepreneurial activity (Estrin et al 2013a(Estrin et al , b, 2016Sahasranamam and Nandakumar 2018;Stephan et al 2015). Moreover, previous research highlights that high-quality formal institutions are usually associated with certain cultural characteristics and socioeconomic development (Inglehart and Welzel 2005;Welzel 2013).…”
Section: Entrepreneurs' Age and Social Value Creation: The Moderatingmentioning
confidence: 98%
“…They influence not only the emergence but also the implementation of such activities in the country. Sahasranamam and Nandakumar (2020) investigated role of a country's formal institutions (financial, educational, political) on the relationship between individual capital (financial, human, social capital) and social entrepreneurship entry. This study showed the nature of contingent effects of formal institutions on the relationship between individual capital and the emergence of social enterprises.…”
Section: Factors Influencing the Involvement In Social Enterprisesmentioning
confidence: 99%
“…Representing a specific socio-economic phenomenon, social entrepreneurship is carried out in a social environment, is regulated by the current legal regulations in the society, and is also subject to the action of economic laws and patterns common to all business entities (Sahasranamam & Nandakumar, 2018). This means that social entrepreneurship is not free from society, but functions in interconnection and interdependence with it.…”
Section: Methodsmentioning
confidence: 99%